Odpowiedzi

2009-11-24T17:12:05+01:00
A) 5(x-2)-(x-3)x+(x-8)x
5x-10-x²+3x+x²-8x=-10
b)-2x(3-x)-(2x²- 6x+3)
-6x+2x²-2x²+6x-3=-3
c) -6x(3x²-1)-3(2x+4)+18x³
-18x³+6x-6x-12+18x³=-12
d)-(12x²+3x-5)+3x(4x+1)-7
-12x²-3x+5+12x²+3x-7=-2

w przypadku D
1 5 1
2009-11-24T18:24:44+01:00
A) 5(x-2)-(x-3)x+(x-8)x=

5x-10-x²+3x+x²-8x=-10

b)-2x(3-x)-(2x²- 6x+3)

-6x+2x²-2x²+6x-3=-3

c) -6x(3x²-1)-3(2x+4)+18x³

-18x³+6x-6x-12+18x³=-12

d)-(12x²+3x-5)+3x(4x+1)-7

e)-12x²-3x+5+12x²+3x-7=-2

najwyzsza wartosc to -2
2 3 2
2009-11-24T19:36:09+01:00
A) 5(x-2)-(x-3)x+(x-8)x = 5x-10-x²+3x+x²-8x = -10
b)-2x(3-x)-(2x²- 6x+3) = -6x+2x²-2x²+6x-3 = -3
c) -6x(3x²-1)-3(2x+4)+18x³= -18x³+6x - 6x-12 +18x³ = -12
d)-(12x²+3x-5)+3x(4x+1)-7 = -12x²-3x+5+12x²+3x-7 = -2

Najwieksza jest w 'd'


Pozdrawiam! :)